Peran Guru PAI Dalam Pembinaan Akhlak Pada Siswa Sekolah Dasar Kelas IV Di SD Negeri 3 Rukti Sediyo - Lusiana Lusiana; Zahratul Fitria; Tria Marvida; Badratun Nafis (Berkala Ilmiah Pendidikan, 2022)
The purpose of this study was to determine the role of PAI teachers in fostering morals in elementary school students. The type of research used is qualitative research. The data sources used are primary and secondary data. Data collection techniques using interviews, observation and documentation. Data analysis technique using triangulation. The results of this study are that teachers are the main figures in the process of implementing educational programs. So that the desired learning objectives can be achieved optimally. The role of the PAI teacher in moral development for grade IV students, including: helping students learn various things they do not know, the class IV PAI teacher also plays a role in providing training and guidance to students so that they have good morals, not only that their role PAI teachers can also be advisors, role models, and provide supervision both in the areas of knowledge and skills.